The experiences of face veil wearers in Europe and the law / edited by Eva Brems. - Brems, Eva (Cambridge studies in law and society., 2014)
One of the most remarkable aspects pertaining to the legal bans and societal debates on the face veil in Europe is that they rely on assumptions which lack any factual basis. To rectify this, Eva Brems researched the experiences of women who wear a face veil in Belgium and brought her research results together with those of colleagues who did the same in four other European countries. Their findings, which are outlined in this volume, move the current discussion on face veil bans forward by providing a much-needed insider perspective. In addition, a number of legal and social science scholars comment on the empirical findings and on the face veil issue more generally.